Epacadostat plus pembrolizumab versus placebo plus pembrolizumab in patients with unresectable or metastatic melanoma (ECHO-301/KEYNOTE-252): a phase 3, randomised, double-blind study. Issue 8 (August 2019) - Long, Georgina V; Dummer, Reinhard; Hamid, Omid; Gajewski, Thomas F; Caglevic, Christian; Dalle, Stephane; Arance, Ana; Carlino, Matteo S; Grob, Jean-Jacques; Kim, Tae Min; Demidov, Lev; Robert, Caroline; et al.
Summary: Background: Immunotherapy combination treatments can improve patient outcomes. Epacadostat, an IDO1 selective inhibitor, and pembrolizumab, a PD-1 inhibitor, showed promising antitumour activity in the phase 1–2 ECHO-202/KEYNOTE-037 study in advanced melanoma. In this trial, we aimed to compare progression-free survival and overall survival in patients with unresectable stage III or IV melanoma receiving epacadostat plus pembrolizumab versus placebo plus pembrolizumab. Methods: In this international, randomised, placebo-controlled, double-blind, parallel-group, phase 3 trial, eligible participants were aged 18 years or older, with unresectable stage III or IV melanoma previously untreated with PD-1 or PD-L1 checkpoint inhibitors, an ECOG performance status of 0 or 1, and had a known BRAF V600 mutant status or consented to BRAF V600 mutation testing during screening. Patients were stratified by PD-L1 expression and BRAF V600 mutation status and randomly assigned (1:1) through a central interactive voice and integrated web response system to receive epacadostat 100 mg orally twice daily plus pembrolizumab 200 mg intravenously every 3 weeks or placebo plus pembrolizumab for up to 2 years. We used block randomisation with a block size of four in each stratum. Primary endpoints were progression-free survival and overall survival in the intention-to-treat population. The safety analysis population included randomly assigned patients who received at least one dose of study treatment. The study was stopped after the second interim analysis; follow-up for safety is ongoing. This study is registered withClinicalTrials.gov, numberNCT02752074 . Findings: Between June 21, 2016, and Aug 7, 2017, 928 patients were screened and 706 patients were randomly assigned to receive epacadostat plus pembrolizumab (n=354) or placebo plus pembrolizumab (n=352). Median follow-up was 12·4 months (IQR 10·3–14·5). No significant differences were found between the treatment groups for progression-free survival (median 4·7 months, 95% CI 2·9–6·8, for epacadostat plus pembrolizumab vs 4·9 months, 2·9–6·8, for placebo plus pembrolizumab; hazard ratio [HR] 1·00, 95% CI 0·83–1·21; one-sided p=0·52) or overall survival (median not reached in either group; epacadostat plus pembrolizumab vs placebo plus pembrolizumab: HR 1·13, 0·86–1·49; one-sided p=0·81). The most common grade 3 or worse treatment-related adverse event was lipase increase, which occurred in 14 (4%) of 353 patients receiving epacadostat plus pembrolizumab and 11 (3%) of 352 patients receiving placebo plus pembrolizumab. Treatment-related serious adverse events were reported in 37 (10%) of 353 patients receiving epacadostat plus pembrolizumab and 32 (9%) of 352 patients receiving placebo plus pembrolizumab. There were no treatment-related deaths in either treatment group. Interpretation: Epacadostat 100 mg twice daily plus pembrolizumab did not improve progression-free survival or overall survival compared with placebo plus pembrolizumab in patients with unresectable or metastatic melanoma. The usefulness of IDO1 inhibition as a strategy to enhance anti-PD-1 therapy activity in cancer remains uncertain. Funding: Incyte Corporation, in collaboration with Merck Sharp & Dohme.